2010
DOI: 10.1088/0256-307x/27/5/056101
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Partial Dislocations in Nanocrystalline Metals

Abstract: Partial dislocations in nanocrystalline metals are introduced and a modified dislocation density formula for partial dislocations is established by x-ray line profile analysis theories. Effects of factors on the determination of partial dislocation density are discussed. From the correlation between the partial and perfect dislocations, partial dislocation density is simply quantitative characterized by drawing on the evaluation methodology of perfect dislocations. Dislocation densities of nanocrystalline nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is well documented that epitaxial crystallization of PCL on oriented iPP substrate results in the formation of a cross‐hatched lamellar pattern with the PCL lamellae ± 40° apart from the molecular chain direction of iPP as illustrated in Figure S8 (Supporting Information). [ 34 , 39 ] In other words, the PCL and iPP chains are inclined to an angle of ± 50°. On the other hand, it has been confirmed that the PEG does not exhibit epitaxial ability on iPP substrate as well.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that epitaxial crystallization of PCL on oriented iPP substrate results in the formation of a cross‐hatched lamellar pattern with the PCL lamellae ± 40° apart from the molecular chain direction of iPP as illustrated in Figure S8 (Supporting Information). [ 34 , 39 ] In other words, the PCL and iPP chains are inclined to an angle of ± 50°. On the other hand, it has been confirmed that the PEG does not exhibit epitaxial ability on iPP substrate as well.…”
Section: Resultsmentioning
confidence: 99%
“…If failure probability of the two approximate planes are equal, then one with the larger correlation coefficient with the main approximation plane will be arranged before the other one. The failure probability of approximation planes system is calculated sequentially by equivalent computation algorithm provided by Lu and Dong [9]. Equivalent condition is the reliability unchanged, and the obtained equivalent approximation plane parallels to the main approximation plane.…”
Section: Multi-plane Combination Methodsmentioning
confidence: 99%
“…The multi-plane combination method is performed by Feng [7] for performance function with strongly nonlinearity, in which approximation plane combination are used to approximate the nonlinear limit state equation, but is only applied for the simple reliability problems. More complex case is developed by Mahadevan and Shi [8], and became a more perfect and practical method through further work by Lu and Dong [9]. The multi-plane combination method is proposed for the limit state function with high nonlinearity to improve calculation accuracy.…”
Section: Introductionmentioning
confidence: 99%